Saint Mariana de Jesús: Between Devotion, Virtue and Quito’s Memory - Morales Barahona, Karen Melissa (Ánima, 2026)
Drawing on the contrast between two pictorial representations of Saint Mariana de Jesús produced during Ecuador’s colonial and republican periods, this article analyzes the transformations of the model of femininity that circulated in each historical context. Through the study of a colonial portrait attributed to Hernando de la Cruz and Joaquín Pinto’s republican painting Santa Mariana catequista (1876), the works are read from the spaces through which the saint’s holiness is imagined and legitimized. Whereas the colonial image centers on penance and on spiritual experience lived out within a private sphere, the republican work relocates the saint into a social space of religious teaching and the community’s moral formation. From a historical-visual perspective, it is argued that this reconfiguration responds to the interests of the power structures of each period. Consequently, the representations of the saint are understood as devices of symbolic construction that articulate religion, gender, and social order, and that reveal the cultural expectations associated with femininity along the proposed timeline.